Exploring the role of chitosan in enhancing poultry production: Benefits and applications (International Journal of Agricultural Research, Innovation and Technology, 2025)
Chitosan (a chitin derived biopolymer) has gained enormous attention due to its potential uses in broiler and layer production. Chitosan is a natural, nontoxic, and biodegradable substance that has several benefits in poultry, i.e., it improves poultry growth, health, and overall productivity. The present review paper explores the versatile roles of chitosan in poultry, exploring its use as an immune-modulator, growth promoter, and natural antimicrobial and antioxidant feed additive. Chitosan biopolymer is reported to boost the immunity FCR (feed conversion ratio) and reduce the chances of diseases working as an antimicrobial compound. Chitosan enhances nutrient digestibility and absorption, maintains gut health, and controls the intestinal microflora. Dietary use of chitosan is well documented to improve meat quality, feather growth, and egg quality as an alternative to synthetic growth promoters and antibiotics. Therefore, this review intends to gather scientific evidence about using chitosan on production performance, health and well-being of poultry and minimizing the impact of production on the environment for sustainable and environmentally healthy production. Moreover, the prospects for research on chitosan in poultry production are also discussed, stressing the need to optimize chitosan applications and address existing limitations.Int. J. Agril. Res. Innov. Tech. 15(1): 22-38, June 2025